Experiencing the shift: How postsecondary contract and continuing faculty moved to online course delivery - Patricia Danyluk; Amy Burns (Brock Education: a Journal of Educational Research and Practice, 2021)
The shift to online learning that occurred in March of 2020, created an unprecedented period of intense work for faculty and sessional instructors at the post-secondary level. This shift necessitated courses be adapted under short timelines, new technology be integrated into course design and teaching strategies and assessment methods be adapted for an online environment (Van Nuland et al., 2020). This study examines how sessional instructors, referred to in this chapter as contract faculty, and continuing full-time faculty members delivering the same online courses experienced this shift. While the demands of a continuing faculty position call for balancing of teaching, research and service responsibilities, contract instructors have their own unique stressors (Karram Stephenson et al., 2020). Contract faculty lack job security, are paid by the course and often receive their teaching assignments with short notice. By examining their perspectives on delivering the same courses online, we learn that the shift to online teaching resulted in additional work in order to adapt courses to the online environment, with faculty describing the challenges of balancing the additional work with other responsibilities of their position. Concerns of participants focused on a perceived inability to develop relationships with students in an online environment.